2020
DOI: 10.1001/jama.2019.21576
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Language of Clinician Distress

Abstract: Neurasthenia was once a diagnosis ubiquitous enough to be household vernacular, but by the 1930s, as physicians became interested in more precise, narrower diagnoses, fewer patients were diagnosed as having this condition. 1 The widespread use of the diagnosis had diluted its utility. In 2019, member states of the World Health Organization accepted the International Classification of Diseases and Related Health Problems, Eleventh Revision, which retired neurasthenia, and replaced this term with bodily distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 7 publications
(9 reference statements)
3
94
0
Order By: Relevance
“…11 Repeated episodes of moral distress in the workplace cause clinicians to become isolated 15 and morally numb to challenging situations, develop a loss of moral identity, and finally succumb to moral injury, where a physician begins to question their own moral framework for continuing to work within the system. 6,16 Studies of both clinicians and nurses find that moral distress cases cause frustration, anger, guilt, anxiety, depersonalization of patients, and finally a high risk for burnout and leaving the profession. 6,[17][18][19][20] With the COVID pandemic in mind, the surge of patients in certain hotspots and the inability of the physician and nurse workforce to keep up with demand, as well as a clinician's fear for his or her own health, is anxiety provoking for all health care providers.…”
Section: Why Is Moral Distress Harmful?mentioning
confidence: 99%
See 3 more Smart Citations
“…11 Repeated episodes of moral distress in the workplace cause clinicians to become isolated 15 and morally numb to challenging situations, develop a loss of moral identity, and finally succumb to moral injury, where a physician begins to question their own moral framework for continuing to work within the system. 6,16 Studies of both clinicians and nurses find that moral distress cases cause frustration, anger, guilt, anxiety, depersonalization of patients, and finally a high risk for burnout and leaving the profession. 6,[17][18][19][20] With the COVID pandemic in mind, the surge of patients in certain hotspots and the inability of the physician and nurse workforce to keep up with demand, as well as a clinician's fear for his or her own health, is anxiety provoking for all health care providers.…”
Section: Why Is Moral Distress Harmful?mentioning
confidence: 99%
“…6,16 Studies of both clinicians and nurses find that moral distress cases cause frustration, anger, guilt, anxiety, depersonalization of patients, and finally a high risk for burnout and leaving the profession. 6,[17][18][19][20] With the COVID pandemic in mind, the surge of patients in certain hotspots and the inability of the physician and nurse workforce to keep up with demand, as well as a clinician's fear for his or her own health, is anxiety provoking for all health care providers. There are things program directors can do, however, to help residents manage this tension and mitigate moral injury.…”
Section: Why Is Moral Distress Harmful?mentioning
confidence: 99%
See 2 more Smart Citations
“…These are situations in which the individual is faced with two moral principles, in opposition to each other, which imply making a decision: maximizing the common good according to a cost-benefit analysis (utilitarian resolution) or deciding for the unconditional respect for a moral rule, regardless of the consequences (deontological resolution). Moral distress occurs when individuals know what is the ethically appropriate choice but they are unable to do it due to external or internal restrictions (McCarthy and Deady, 2008;Epstein and Hamric, 2009;Dean et al, 2020;Dunham et al, 2020). During an emergency like a pandemic, some decisions are made under stress and several studies showed that stress can influence moral decision-making (Lützen et al, 2010;Starcke et al, 2011;Starcke and Brand, 2012;Youssef et al, 2012;Romero-Rivas and Rodríguez-Cuadrado, 2020).…”
Section: Introductionmentioning
confidence: 99%